(untitled) (The Journal of DMC, 2026)
Indigenous knowledge is a dynamic and holistic system rooted in daily life, spirituality, and ancestral wisdom. Among the Kirat Rai community of Nepal, this knowledge is embodied in the Mundumic Suptulung, a flexible oral tradition that evolves with time while preserving indigenous theories, values, and ancestral teachings. Practiced through songs, myths, legends, and proverbs, it serves as a living archive of cultural identity and practical education. Rituals involving spiritual leaders such as Mangpa, Nachhung, and Fedangma are central to this transmission, offering experiential learning that connects the community to its ancestors. Ceremonies like Sakela, Sopuiya, Sakenwa, and Deuha reflect the community’s values and their intimate relationship with nature. The use of Khabai/Babkha a traditional food and ritual offering symbolizes the adaptation of ancestral practices and the integration of nature into daily life. Its preparation and ritual use are themselves forms of indigenous pedagogy, emphasizing the importance of hands-on learning over textual instruction. The Kirat Rai worldview sees nature not only as a resource but as a sacred space where ancestors dwell and blessings are received. Thus, indigenous education within this community is inherently ecological, spiritual, and practical, fostering curiosity and lifelong learning. The Mundumic Suptulung is more than a cultural narrative it is a guiding framework for living a good life, adapting to change, and sustaining identity through nature-based wisdom and ancestral reverence.